Carotenoid biosynthesis regulatory mechanisms in plants - Othman, Rashidi; Mohd Zaifuddin, Fatimah Azzahra; Mohd Hassan, Norazian (Japan Oil Chemists' Society, 2014)
Carotenoids are bioactive compounds with remarkably special properties produced by plants in response to internal and external stresses. In this review paper, we focus on the subject of carotenoid biosynthesis and several factors that have been reported to significantly enhance or reduce carotenoid accumulation in studied plant species. These factors include varietal aspects, location, growing season, and type of stress experienced by a plant. In addition, we propose that there are three stress.